Occurrence of SARS-CoV-2 in the intraocular milieu. (December 2020) - List, Wolfgang; Regitnig, Peter; Kashofer, Karl; Gorkiewicz, Gregor; Zacharias, Martin; Wedrich, Andreas; Posch-Pertl, Laura
Abstract: The purpose of this research is to study the intraocular occurrence of SARS-CoV-2. In postmortem examinations, aqueous humor and the vitreous samples were collected. All individuals were previously positive in nasopharyngeal swabbing and cause of death was respiratory failure due to SARS-CoV-2 infection. Testing was done using quantitative RT-PCR. We included 16 aqueous humor and 16 vitreous samples for PCR testing. None of the results was positive for SARS-CoV-2. Human GAPDH genes to verify the presence of RNA was present in all aqueous humor samples (16/16, 100%) and 15/16 (93.8%) vitreous samples. In conclusion, this case series found no evidence of SARS-CoV-2 in the intraocular milieu. Highlights: Manifestation of SARS-CoV-2 in the intraocular milieu. Manifestation of SARS-CoV-2 in the vitreous. Manifestation of SARS-CoV-2 in the aqueous humor.